Personal Branding Airlangga Hartarto Dalam Membangun Elektabilitas Sebagai Calon Presiden - Hermanto, Bambang; Rasul, Najmuddin; Hadiati, Hadiati (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This research is based on the candidacy of the general chairman of the Golkar Party, Airlangga Hartarto, in the upcoming 2024 election, which has not shown an increase in electability as a presidential or vice-presidential candidate despite carrying out various forms of personal branding through Instagram social media accounts. This study uses a qualitative research method with an analytic-descriptive approach to provide a description of an object of research. Furthermore, in interpreting each post's content on the Instagram social media platform, the @airlanggahartato_Official account, the author uses a qualitative content analysis (QCA) approach. Using two data collection techniques, namely observation and documentation, and three stages of data analysis, namely data collection/data reduction, presentation, and verification/conclusion.The results of this study indicate that the @airlanggahartarto_official account uses three strategies in a post, namely: 1) clarity, 2) specialization, and 3) Consistency. Meanwhile, in terms of forming personal branding to increase Airlangga Hartarto's electability, it can be seen in three variables, namely segmenting, targeting, and positioning. However, the personal branding that has been built has not been able to raise Airlangga Hartarto's overall popularity and electability to run as a Presidential Candidate.